Assessment of dispersion correction methods within density functional theory for energetic materials. Issue 7 (3rd May 2017) - Fan, Jun-Yu; Zheng, Zhao-Yang; Su, Yan; Zhao, Ji-Jun
Abstract: Accurate description of the non-covalent intermolecular interaction is significant for the study of energetic materials. Here, the performance of a variety of dispersion correction methods within density functional theory (DFT) is assessed carefully for six energetic molecular crystals using experimental data as benchmark. We consider semi-empirical DFT plus dispersion correction methods (DFT-D, including DFT-D2 and DFT-D3) and non-empirical van der Waals density functional correction methods (including vdW-DF, vdW-DF2, optPBE-vdW, optB88-vdW and optB86b-vdW). The calculative cell volume, lattice energies, pressure-induced change of volume and bulk modulus are compared with the available experimental data. At ambient condition, theoretical cell volumes by optPBE-vdW, PBE-D3 and vdW-DF2 are in reasonable accordance with experimental data, while PBE-D3 and vdW-DF2 give satisfactory for lattice energies. Under high pressure, both semi-empirical PBE-D3 and non-empirical vdW-DF2 methods could yield reliable results, in which the results by PBE-D3 have smaller deviation from experiment than vdW-DF2 in the entire pressure range. Furthermore, bulk modulus by PBE-D3 calculations also compares reasonably with experimental data. These present assessments provide valuable guidelines for selecting the appropriate method to investigate physical and chemical proprieties of energetic materials in the future.